Hepatocellular Mitochondrial Alterations in Patients With Chronic Hepatitis C: Ultrastructural and Biochemical Findings - Barbaro, Giuseppe; Di Lorenzo, Gabriella; Asti, Annalia; Ribersani, Michela; Belloni, Giancarlo; Grisorio, Benvenuto; Filice, Gaetano; Barbarini, Giorgio (The American journal of gastroenterology, 1999)
Hepatitis C virus (HCV) infection is associated with increased lipoperoxidation, which may lead to interference with mitochondrial function with possible depletion of mitochondrial DNA (mtDNA). We correlated the ultrastructural findings of liver biopsy specimens with the lipoperoxidation markers and contents of mtDNA in chronic hepatitis C (CHC) patients with a different HCV genotype. Liver biopsy samples obtained from 75 CHC patients were processed for histological and electron microscopic examination. Twenty-two subjects without known liver disease served as controls. Hepatic glutathione in its reduced (H-GSH) and oxidized (H-GSSG) forms were determined from biopsy specimens by high-performance liquid chromatography. Plasmatic and lymphocytic GSH and erythrocytic malonyldialdehyde (MDA) were also determined, along with the ratio between mtDNA and nuclear DNA (nDNA). Ultrastructural alterations of the mitochondria were documented in 23 patients with genotype 1b, compared with 15 patients with genotype 2a/2c (p= 0.020) and seven patients with genotype 3a (p < 0.001). A significant depletion of H-GSH and lymphocytic GSH, an increase of H-GSSG and MDA, and a reduction of the mtDNA/nDNA ratio were documented in patients with genotype 1b, compared with patients with genotype 2a/2c and 3a and with controls. In patients with genotype 1b frequent ultrastructural alterations of the mitochondria may be observed, and the depletion of mtDNA in these patients may represent the expression of a greater impairment of the process of oxidative phosphorylation. An increased production of free radicals in patients with genotype 1b may influence the evolution of the liver disease by enhancement of the cytopathic effect of HCV.